PTH-032 D2 biopsies in weight loss referrals – is it necessary and cost effective?. (22nd June 2015) - Kotha, S; Holohan, C; Gera, A; Loganayagam, A
Abstract : Introduction: Biopsies from the second part of the duodenum (D2) are commonly taken in patients undergoing upper GI endoscopy for weight loss. This is done as weight loss can be an important presentation of coeliac disease. Both BSG (British Society of Gastroenterology) and NICE (National Institute for Health and Care Excellence) guidelines recommend that patients with suspected coeliac disease should be screened with serology initially. If coeliac serology is negative then small bowel biopsies are generally not necessary. Despite this D2 are routinely taken. Random duodenal biopsies result in increased workload and cost. The aim of this study was to determine if D2 were necessary and cost effective in every patient undergoing an oesophagogastroduodenoscopy (OGD) for weight loss. Method: We analysed retrospective data collected from ADAM (endoscopy database) at Queen Elizabeth Hospital for a period of 1 year (2013) for all the OGDs and D2 undertaken with the referral indication of weight loss. Demographic data, endoscopic findings, histological findings and cost of analysing histology were evaluated. Results: 236 patients underwent OGD during the study period under the referral indication of weight loss. All 236 patients had D2 taken. 4 patients were excluded (2 had a prior diagnosis of coeliac and 2 did not have histology results on our system).15 patients (6.5%) had positive histology. 2 patients (0.8%) had evidence of coeliac disease on histology, but both had evidence of iron deficiency anaemia in addition to weight loss. 2 patients had intraepithelial lymphocytes but normal villi and negative serology (not treated as coeliac disease as patients were asymptomatic and gaining weight). 1 patient has giardia on the biopsy. 1 patient had mild villous blunting, but had metastatic lung disease and was not followed up in our clinic. 9 patients (3.8%) had non-specific duodenitis on biopsy. The overall pick up rate for significant pathology on D2 was only 2.5%. Conclusion: The pickup rate for significant pathology on D2 for weight loss was poor. The 2 patients with definitive diagnosis of coeliac also had evidence of iron deficiency anaemia. The cumulative cost of analysing these biopsies was £ 7775(£33.6/biopsy). Despite this patients with weight loss seem to have D2 rather than serological testing. This may be due to the fact that majority of these patients undergo an OGD and it was considered easier to perform D2 at the same time. However, this increases the burden of cost on the health care services. D2 should only be performed in patients undergoing an OGD for weight loss, if coeliac serology is positive or there is a high index of suspicion for coeliac disease. Disclosure of interest: None Declared.